HUBUNGAN RIWAYAT MENYUSUI DENGAN KEJADIAN KANKER PAYUDARA DI RSUD RAJA AHMAD TABIB TANJUNGPINANG - Sarinaex, Marlia; Yunita, Prasida; Santi, Yollanda Dwi (Universitas Batam, 2021)
Breast cancer is a cancer that comes from glands, glandular ducts, and breast support tissues. Based on Global Cancer Observatory 2018 data from the World Health Organization (WHO), breast cancer has 58,256 cases or 16.7% of the total 348,809 cancer cases with a mortality rate in developing countries of 324,000 (14.3% of the total) and in developed countries as many as 198,000 (15.4% of the total).One of the risk factors for breast cancer is a history of breastfeeding. This study analyzed the relationship between the history of breastfeeding and the case of breast cancer at Raja Ahmad Tabib Regional Public Hospital in Tanjungpinang. The variables of this study were breastfeeding history and breast cancer case. A method used in this research was analytical observational research design with cross sectional approach.The number of samples is 56. The data was collected by interviewing the samples using questionnaires. The data was analyzed by using Chi-square test.Based on the statistical test, it was found that as many as respondents with breast cancer, there were 4 respondents who had a history of breastfeeding â‰¥1.5 years, and respondents without breast cancer who had a history of breastfeeding â‰¥1.5 years were 53.6%.The results of bivariate analysis with the chi-square test obtained a value of 0.002, which means that there is a significant relationship between breastfeeding history and the breast cancer case.Based on the result of this study, it can be concluded that there is a significant correlation between the breastfeeding history and breast cancer case at Raja Ahmad Tabib Regional Public Hospital of Tanjungpinang in 2020.